The impact of politics on lexical coinage: A study of the morphological patterns in Egyptian printed media after January, 25th 2011 - Lotfy, Hagar (AUC Knowledge Fountain, 2017)
All living languages come across linguistic changes with time. It is important to mention that various linguistic phenomena that living languages encounter include sound change, phonological change, syntactic change, lexical change or semantic change. From 2011 to 2015, Egypt passed through a critical political situation; a result, media and press introduce new lexical items and revive lexical terminology from the past. During the Arab Spring media websites tried to offer the most accurate lexical terminologies that express people’s impatience for dignity, socio-political reforms, and human rights (Michel, 2013). This study aims to primarily investigate the impact of the political situation on the media lexical production, and the word formation strategies that has been frequently used to coin lexical items. Thus, this paper tries to answer the following research questions: 1. to what extent does political change influence the process of lexical creation. What are the common strategies used in lexical creation in modern written Arabic. The data is extracted by scanning opinion columns in al-Ahram and Al-Shorouq newspapers from 2009 to 2015. Preliminary results demonstrate that socio-political variables influence the lexical production in which the language used incorporates the social and political feelings. Moreover, from data analysis, the study gives an updated definition of compounding, as a word formation process, and highlights the grammatical structures and the linguistic functions of compounding in MSA which vary from that produced by Arabic Academies. The Results also illustrate that the most common strategies adopted to create lexical items are compounding, as most used strategy, followed by derivation. The paper ends with pedagogical implications for strategies of teaching vocabulary in classroom.